Penal code = قانون العقوبات - Egypt (The Middle East Library for Economic Services, 2025)
Law No. 58 Of The Year 1937 Promulgating The Penal Code Book-One General Provisions Part-1 General Rules.. Types Of Crimes... Part-2 Part-3 Penalties...... Section 1: Original Penalties. Section-2: Ancillary Penalties. Section 3: Plurality Of Penalties. Part-4 Complicity Of Several Persons In One Crime. Part-5 Part-6 Attempt.... Criminal Agreements. Part-7 Recidivism... Part-8 Conditional Execution Of Rulings.. Part-9 Permissibility Causes And Penalty Preventives... Part-10 Juvenile Delinquent....... Remission Of Sentence And Comprehensive Remission.. Part-11 Book - Two Felonies And Misdemeanors Prejudicial To The Public Interest And Their Penalties Felonies And Misdemeanors Harmful To The Government's Part-1 Security From A Source Abroad..... Felonies And Misdemeanors Internally Prejudicial To The Part-2 6 6 Government. Section 1 Section-2 Explosives... Part-2 (Bis) Part-3 Part-4 Bribery. Defalcation, Encroachment On, And Peculation Of Public Funds.. Part-5 Excess Of Position Limits By Officials, And Laches In Performing Their Position Related Duties.... Part-6 Coercion And Ill-Treatment By Public Officials To Individuals Of The People... A [6:08 PM, 12/29/2021] Kholoud: Page 1 Part-7 Opposing The Rulers, Disobeying Their Orders, And Outraging Them With Curse And Other Abuse Part-8 Part-9 Escape Of The Jailed And Hiding The Felons. Breaking The Seals, Stealing The Deposited Documents And Official Papers............. Part-10 Embezzlement Of Titles And Positions, And Characterizing Oneself Thereby In An Unlawful Shape Part-11 Misdemeanors Connected With Religions. Part-12 Damaging The Buildings, Monuments, And Other Public Objects. Part-13 Interruption Of Communications. Part-14 Crimes Occurring By Means Of Newspapers And Others. Part-15 Coins And Spurious Specie. Part-16 Forgery. Part-17 Trading In Banned Objects, And Counterfeiting Postmarks And Telegraphmarks... Book-Three Felonies And Midemeanors Occuring To Individuals Killing, Wounding, And Beating.. Part - 1 Part-2 Arson....... Part-3 Abortion Of Pregnants, Manufacture And Sale Of Adulterated Syrups Or Drugs That Are Noxious To Health Indecent Assault And Corruption Of Morals. Arrest Of People And Jailing Them Without Any